PENGARUH KNOWLEDGE MANAGEMENT TERHADAP PEMBERDAYAAN DOSEN: STUDI KASUS DOSEN PERGURUAN TINGGI SWASTA JAKARTA - Ahmad Husin (Operations Excellence: Journal of Applied Industrial Engineering, 2017)
Knowledge Management is a field that attracts a lot of attention both among academics and practitioners. Awareness of applying knowledge management to business strategies is needed because it is proven that companies that make knowledge resources as their main asset are always able to drive companies more innovative towards their competitors, in the knowledge management education industry is a very important asset because knowledge can be captured, codified or stored. This study aims to analyze the influence of knowledge creation, knowledge storage, knowledge sharing and knowledge application on the empowerment of lecturers. Testing the hypothesis in this study using SPSS 23 software. The results showed that knowledge creation and knowledge application affect the empowerment of lecturers, while knowledge storage and knowledge sharing have no effect on the empowerment of lecturers. The implication of the research results is the need to develop knowledge in universities through interaction with other lecturers in the campus environment to encourage the knowledge that is created maintained and sustainable.